The Impact of Corporate Carbon Footprint on Financial Performance of Manufacturing Industry in Malaysia - Khairunnisa, Ibrahim (UNIMAS, 2024)
Environmental sustainability has become a key concern for businesses worldwide, with expectations for them to take responsibility for their carbon emissions and environmental effects. The current study predominantly focuses on the energy sector, with less attention given to manufacturing in Malaysia. Reducing carbon emissions is critical for businesses due to both regulatory pressures and market expectations. Companies that proactively decrease emissions often see improved financial performance through greater sales, better access to finance, and increased efficiency. This study aims to provide significant insights into the sustainability practices of corporations and their influence on financial performance. Companies listed on Bursa Malaysia were chosen as the sample data in this study to evaluate and investigate the relationship between carbon footprint and financial performance. Approximately 18.97%, 269 of respondents are willing to disclose their carbon footprint information, suggesting a relatively low level of carbon footprint reporting. The results of the random effects model indicate that the null hypotheses for Return on Assets (ROA), Return on Equity (ROE), and Return on Investment (ROI) are accepted. The policymakers should provide incentives for investment in green technology and enact strict regulations to encourage more companies to engage in carbon reporting. Keywords: Corporate Carbon Footprint, Financial Performance, Sustainability, Environmental Impact.